Menyemai Harmoni Sosial dalamTradisi Haul Di Desa Ujung-Ujung Kecamatan Pabelan-Semarang - Wahyu Hidayat; Friska Aritonang (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
This study aims determine the benefits of the Haul tradition to counter intolerance and religious nuances that are rife in Indonesia through the Haul tradition in Ujung-ujung village. Ujung-Ujung Village is a Javanese community that has a tradition called haul, The increasing number of visitors encouraged the committee to introduce culture and culinary specialties from Ujung-Ujung Village, through a cultural parade and bazaar in the middle of the haul event. This development requires the awareness of all villagers to work together to succeed in the success of the haul that has become the common property. This is where the interaction and social harmony of citizens are created which is inseparable from the influence of the Javanese cultural character that the Ujung-Ujung people live on. Haul Eyang Muhyidin, who has become an annual compulsory ritual, has also transformed society into a symbol full of meaning. This tradition has become a symbol of harmonious social life.